Katekese Digital dalam Membangun Spirit Toleransi bagi Generasi Z di Tengah Budaya Media Sosial - Karolina Suwul; Monica Innanda C; Intansakti Pius X (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
This study aims to examine the role of digital catechesis in fostering a spirit of tolerance among Generation Z within the context of social media culture. The method used is a literature review with a descriptive qualitative approach through the analysis of various relevant sources, including Church documents and other scholarly works. The findings indicate that the development of digital technology has transformed the way the Church carries out its mission of evangelization, making digital catechesis an effective, contextual, and accessible medium for young people. Generation Z, as digital natives, has a strong attachment to social media, which functions not only as a communication tool but also as a space for identity formation and understanding diversity. Social media provides opportunities to cultivate tolerance through interactions across cultures, religions, and perspectives, but it also presents challenges such as the spread of misinformation, hate speech, and intolerance. In this context, digital catechesis plays an important role in instilling Christian values such as love, respect for differences, and critical thinking skills. Therefore, digital catechesis becomes a strategic means of forming young people who are faithful, wise, tolerant, and able to live harmoniously.